2020
DOI: 10.24875/ciru.20001096
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia de malformaciones y deformidades congénitas del sistema osteomuscular en recién nacidos vivos en México, 2008-2017

Abstract: Estimar para México la prevalencia nacional de MDCSOM en nacidos vivos (NV), por entidad federativa y municipio, y analizar su distribución espacial por esas mismas delimitaciones territoriales. Método: Se integró una base de datos de 20,175,422 NV en 2008de 20,175,422 NV en -2017. Se calcularon porcentajes y prevalencias por ámbito nacional, entidades federativas y municipios, con intervalos de confianza al 95%. Se elaboraron mapas y se estratificaron las prevalencias. Resultados: La tasa de prevalencia de m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This figure is similar to estimates made in another study conducted in Mexico (2017) that used different data sources to estimate prevalence at birth rates. 16 Worldwide, several studies have reported CL/P prevalence at birth from nationwide databases. A 2016 study conducted in Brazil reported a national prevalence at birth rate of 0.48 per 1000 live births 17 ; in Colombia, 0.60 per 1000 live births 18 ; and in Canada, 0.82 per 1000 live births.…”
Section: Discussionmentioning
confidence: 99%
“…This figure is similar to estimates made in another study conducted in Mexico (2017) that used different data sources to estimate prevalence at birth rates. 16 Worldwide, several studies have reported CL/P prevalence at birth from nationwide databases. A 2016 study conducted in Brazil reported a national prevalence at birth rate of 0.48 per 1000 live births 17 ; in Colombia, 0.60 per 1000 live births 18 ; and in Canada, 0.82 per 1000 live births.…”
Section: Discussionmentioning
confidence: 99%
“…In our population, 69.42% of the patients are male, which coincides with reports from Contreras et al, Garcia et al and Navarrete. [2][3][4] In Perez et al study, the frequency of cleft lip and palate in hospitals across different regions of the country showed a similar frequency between both sexes (47.8% females and 52.2% males), unlike other studies that included only a single region of the country. 5 In Mexico, the incidence of non-syndromic cleft lip and palate ranges from 0.01 to 1.42 per 1,000 live births.…”
Section: Discussionmentioning
confidence: 99%